A diagnostic for evaluating collaborative responses to compound emergencies. (December 2022) - Bodin, Örjan; Nohrstedt, Daniel; Orach, Kirill
Abstract: The burgeoning literature on compound disasters has advanced the understanding on the causes and drivers of multiple hazard events. Yet, so far, this literature has provided limited insights concerning how multiple hazard events, triggering compounded emergencies, challenge emergency response systems. Here we develop a diagnostic to assess specific challenges facing response systems when confronted with spatially and/or temporally compounded hazard events. The diagnostic comprises three elements. First, compound emergency scenarios are defined based on biophysical links within and between communities, and/or temporal overlap between hazardous events. Second, by drawing from recent public administration literatures, we develop a network-centric model of an emergency response system consisting of actors, venues and functions. Third, we formulate a set of diagnostic questions to specify whether and how compound emergencies challenge response systems. These advances together form a diagnostic tool for researchers as well as practitioners to identify potential weak spots in emergency response systems. The diagnostic also helps assessing what cognitive, preparatory, and planning capacities are needed to ensure more effective responses to compound emergencies. Highlights: Hazards events resulting in compound emergencies are expected to become more prevalent. There is limited knowledge about how compound emergencies affect response systems. A diagnostic tool to partition and assess challenges arising from compounded versus single emergencies is presented. The diagnostic can unveil potential weak spots and capacity needs in an emergency response system.